Addition of mushroom powder to pasta enhances the antioxidant content and modulates the predictive glycaemic response of pasta. (30th October 2018) - Lu, Xikun; Brennan, Margaret A.; Serventi, Luca; Liu, Jianfu; Guan, Wenqiang; Brennan, Charles S.
Highlights: Mushroom powder is a good source of protein, fat and fibre compared to semolina. Addition of mushroom powder decreased the starch digestibility of pasta. Incorporate of mushroom powder enhanced the antioxidant contents of pasta. Abstract: This study reports the effects of addition of mushroom powder on the nutritional properties, predictive in vitro glycaemic response and antioxidant potential of durum wheat pasta. Addition of the mushroom powder enriched the pasta as a source of protein, and soluble and insoluble dietary fibre compared with durum wheat semolina. Incorporation of mushroom powder significantly decreased the extent of starch degradation and the area under the curve (AUC) of reducing sugars released during digestion, while the total phenolic content and antioxidant capacities of samples increased. A mutual inhibition system between the degree of starch gelatinisation and antioxidant capacity of the pasta samples was observed. These results suggest that mushroom powder could be incorporated into fresh semolina pasta, conferring healthier characteristics, namely lowering the potential glycaemic response and improving antioxidant capacity of the pasta.